REDESAIN BODY MOBIL MATARAM PROTO V5 DENGAN MEMPERTIMBANGKAN ASPEK AERODINAMIS - Aji Pranoto; Septa W; Yudha Orienta; Wisnu Y Santika (Universitas Negeri Yogyakarta, 2021)
The Energy Saving Car Contest (KMHE) is a contest organized by the Ministry of Research, Technology and Higher Education (Kemenristekdikti). This is a contest among students to make a national level fuel efficient vehicle. The purpose of designing this design is to produce an energy-efficient car body design